2022
DOI: 10.1186/s12871-022-01704-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety during anesthesia in Ukraine: national audit results

Abstract: Background Although anesthesiologists are one of the leaders in patient safety, anesthesia in low and low-middle income countries still need improvement in safety mesures with evidence-based practice application. The study aim was to audit the safety principles implementation in the Ukrainian anesthesiologist`s practice. Methods The study was held in March 2021-Februrary 2022 by filling out an online questionnarie. The link to the survey was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The first direct use of ultrasound for a regional block was reported in 1994, again for supraclavicular brachial plexus block [9]. Recent studies have demonstrated the cost-effectiveness of ultrasound-guided regional anesthesia in daily clinical practice [10], but it's still not widely available in the operation rooms of some hospitals in Ukraine and in European countries, which was demonstrated in our previous investigation of patient safety during anesthesia in Ukraine [3].…”
Section: Responsesmentioning
confidence: 98%
“…The first direct use of ultrasound for a regional block was reported in 1994, again for supraclavicular brachial plexus block [9]. Recent studies have demonstrated the cost-effectiveness of ultrasound-guided regional anesthesia in daily clinical practice [10], but it's still not widely available in the operation rooms of some hospitals in Ukraine and in European countries, which was demonstrated in our previous investigation of patient safety during anesthesia in Ukraine [3].…”
Section: Responsesmentioning
confidence: 98%
“…It is already believed that quality of life is a characteristic of physical, psychological, emotional and social functioning based on subjective perception [19,24]. Involuntarily, a parallel emerges with the general definition of pain, which was updated in 2020 by the International Association for the Study of Pain (IASP) for the first time since 1979: pain is an unpleasant sensory and emotional experience associated with or seemingly associated with actual or potential tissue damage [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%